Rise of Quad as a ‘Premier Regional Grouping’ - Vibhanshu Shekhar (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2022)
The rise of the Biden Administration in the United States has coincided with the rise of Quad as a ‘premier regional grouping’ in the Indo-Pacific region with a robust agenda of cooperation that spans across strategic, economic, technological, environmental and developmental areas. The Quad’s ambitious agenda underpins the member-states’ deliberate effort to align its two foundational bases – balancing and normative – in the grouping’s outlook. The new Quad aims at achieving three-fold objectives – limiting China’s growing influence and assertive behaviour, augmenting new technological capacity of its member-states and projecting the grouping as a provider of regional good. However, the Quad continues to face various challenges, which relate to both the intent and functional capacity of the member-states and limit the grouping’s effectiveness in achieving its vastly ambitious agenda. The success of the Quad as an informal regional grouping will depend on the member-states’ willingness to overcome differences and navigate across diverse strategic priorities to chart a shared journey.